2012
DOI: 10.1002/ptr.4612
|View full text |Cite
|
Sign up to set email alerts
|

Comfrey: A Clinical Overview

Abstract: Comfrey has a centuries-old tradition as a medicinal plant. Today, multiple randomized controlled trials have demonstrated the efficacy and safety of comfrey preparations for the topical treatment of pain, inflammation and swelling of muscles and joints in degenerative arthritis, acute myalgia in the back, sprains, contusions and strains after sports injuries and accidents, also in children aged 3 or 4 and over. This paper provides information on clinical trials and non-interventional studies published on comf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 35 publications
0
50
0
3
Order By: Relevance
“…These are listed in Table 1 alongside numbers of potentially relevant full texts retrieved from each data source. 31 were also screened. The updated overview 32 was not published at this point.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…These are listed in Table 1 alongside numbers of potentially relevant full texts retrieved from each data source. 31 were also screened. The updated overview 32 was not published at this point.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…A brief summary of its pharmacological properties concluded that comfrey may be a promising strategy for treating skin conditions 29 ; and a systematic review of herbal therapies for osteoarthritis found moderate evidence for the effectiveness of comfrey cream. 30 However, the only current reviews of comfrey that explore the evidence for a range of indications are descriptive overviews of clinical study findings 31,32 written by an employee of a comfrey product manufacturer. Neither review reports the search strategy or risk of bias for each study; consequently, the quality and breadth of the literature is unclear.…”
mentioning
confidence: 99%
“…S. officinale has been commonly used in folk medicine for the treatment of diarrhea, bronchitis, tuberculosis, ulcers, and hemorrhoids. The plant extract was reported to be used as an ointment to promote the wound healing, reduce the inflammation, for the treatment of broken bones, tendon damages, painful joints, and muscles [17]. Although Comfrey also contains dehydropyrrolizidine alkaloids (DHPAs) because of which its internal application is not recommended [18].…”
Section: Introductionmentioning
confidence: 99%
“…Allantoin (5-ureidohydantoin) has numerous widely cited pharmacological uses, including wound healing (9), anti-irritation, hydration and regeneration of tissue (9) and cell proliferation (10), as well as having analgesic (11), keratolytic (12) and epithelially stimulating effects (11). Although allantoin has been used for over 70 years, especially as a wound healer, not enough clinical trials exist and so its mechanism of action remains unknown (13).…”
Section: Discussionmentioning
confidence: 99%